SLIM_GSGP - Vanneschi, Leonardo (2024)
Vanneschi, L. (2024). SLIM_GSGP: The Non-bloating Geometric Semantic Genetic Programming. In M. Giacobini, B. Xue, & L. Manzoni (Eds.), Genetic Programming: 27th European Conference, EuroGP 2024, Held as Part of EvoStar 2024 Aberystwyth, UK, April 3–5, 2024 Proceedings (pp. 125-141). (Lecture Notes in Computer Science; Vol. 14631). Springer Nature Switzerland AG. https://doi.org/10.1007/978-3-031-56957-9_8 --- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS